Subjective evaluation of the functional well-being of an athlete with a disability: key features, dependability, and external validity - Zakharova N. L.; Kotovskaya S. V.; Belenkova L. Yu. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creation and validation of a questionnaire-based approach to assess the performance of athletes with disabilities, focusing on the functionality of their body systems in relation to the demands of their sport.